YKL-40 as a Novel Factor Associated with Inflammation and Catabolic Mechanisms in Osteoarthritic Joints - Tuija Väänänen; Anna Koskinen; Erja-Leena Paukkeri; Mari Hämäläinen; Teemu Moilanen; Eeva Moilanen; Katriina Vuolteenaho (Hindawi Limited, 2014)
YKL-40 is associated with tissue injury and inflammation, and consequently to diseases in which these mechanisms lead to tissue degradation, for example, asthma and rheumatoid arthritis. The purpose of the present study was to investigate if YKL-40 is also a significant factor in osteoarthritis (OA) by assessing associations of YKL-40 with mediators related to the pathogenesis of OA: cartilage destructing matrix metalloproteinases (MMPs) and proinflammatory cytokines interleukin-6 (IL-6) and interleukin-17 (IL-17). Cartilage, synovial fluid (SF), and plasma samples were obtained from 100 OA patients undergoing total knee replacement surgery. SF levels of YKL-40 (1027.9 ± 78.3 ng/mL) were considerably higher than plasma levels (67.2 ± 4.5 ng/mL) and correlated with YKL-40 released from cartilage samples obtained from the same patients (r=0.37, P=0.010), indicating that YKL-40 is produced by OA cartilage. Interestingly, YKL-40 concentrations in OA SF correlated positively with MMP-1 (r=0.36, P=0.014), MMP-3 (r=0.46, P=0.001), IL-6 (r=0.57, P<0.001), and IL-17 (r=0.52, P=0.010) levels. Moreover, IL-6 and IL-17 enhanced YKL-40 production in human primary chondrocyte cultures. The present study introduces YKL-40 as a cartilage-derived factor associated with mediators of inflammation and cartilage destruction involved in the pathogenesis of OA.